Difficult Aspects of Reading Comprehension Faced by Non-English Department of Vocational Students - Abiyyu, Muhammad Bagus; Muth’im, Abdul; Yamin, Mohammad (Universitas Muhammadiyah Kalimantan Timur, 2024)
Understanding and interpreting text is a fundamental skill for students across disciplines, not limited to those in the English Department. Proficiency in reading comprehension not only enhances vocabulary and writing abilities but also fosters overall academic growth. This research endeavors to pinpoint the primary challenges encountered by first-semester students at Politeknik Negeri Banjarmasin in comprehending written material. Employing a descriptive quantitative approach, the study aims to identify the most daunting aspects of reading comprehension. A reading comprehension assessment comprising 40 multiple-choice questions, administered via Google Form, was utilized to gather data. Analysis revealed that students encounter significant hurdles in this domain. Across all question types, spanning the five facets of reading comprehension, difficulty levels were consistently high. Particularly, questions assessing the determination of the main idea posed the greatest challenge, with 60% of students struggling in this area, followed by making inferences (44%), locating references (41%), understanding vocabulary (36%), and grasping detailed information (34%). Notably, identifying the main idea emerged as the most formidable task, whereas discerning detailed information proved relatively less challenging. These findings serve to highlight areas for improvement in understanding main ideas and inform strategies aimed at enhancing comprehension skills.